EFFECT OF DYNAMIC STRETCHING ROUTINE PROGRAM ON LOWER BODY MUSCULAR PREPARATION AND FLEXIBILITY OF FOOTBALL PLAYERS - Deore, Dr. Manish M. (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The aim of this study was to find out effect of dynamic stretching routine program on lower body muscular preparation and flexibility of football players. It was an experimental study in which equivalent groups design was used. In this study 30 intercollegiate malefootball players were selected as sample by using purposive sampling techniquetotal intercollegiate male football players(n=30) from Nashik city. Footballers equally divided into the 15 each experimental and control group. Static flexibility test - ankle, Static flexibility test- hip & trunk used for pre-test were conducted on both the groups prior after implemented dynamic stretching routine program conducted post test obtained collected data was analyzed by using independent sample t-test. Result dynamic stretching routine program was effective to improve muscular flexibility. This shows the significant effect at 0.05 level thus researcher concludes that there was significant improvement on flexibility performance of experimental group as compared to control group due to the treatment given.